Eight Years of TIGRE Robotic Spectroscopy: Operational Experience and Selected Scientific Results - González-Pérez, José Nicolás; Mittag, Marco; Schmitt, Jürgen H. M. M.; Schröder, Klaus-Peter; Jack, Dennis; Rauw, Gregor; Nazé, Yaël (Frontiers in Astronomy and Space Sciences, 2022)
TIGRE (Telescopio Internacional de Guanajuato Robótico Espectroscópico) has been operating in fully robotic mode in the Observatory La Luz (Guanajuato, Mexico) since the end of 2013. With its sole instrument, HEROS, an échelle spectrograph with a spectral resolution R∼20000, TIGRE has collected more than 48000 spectra of 1151 different sources with a total exposure time of more than 11000 hours in these eight years. Here we briefly describe the system and the upgrades performed during the last years. We present the statistics of the weather conditions at the La Luz Observatory, emphasizing the characteristics that affect the astronomical observations. We evaluate the performance and efficiency of TIGRE, both optical and operational, and describe the improvements of the system implemented to optimize the telescope’s performance and meet the requirements of the astronomer in terms of timing constraints for the observations and the quality of the spectra. We describe the actions taken to slow down the optical efficiency loss due to the aging of the optical surfaces as well as the upgrades of the scheduler and the observing procedures to minimize the time lost due to interrupted observations or observations that do not reach the required quality. Finally, we highlight a few of the main scientific results obtained with TIGRE data.